Bioengineering of lanthipeptides in Escherichia coli: assessing the specificity of lichenicidin and haloduracin biosynthetic machinery - Caetano, T.
The lichenicidin and haloduracin biosynthetic machinery specificity was investigated invivo in Escherichia coli. Unlike previous reports using different hosts, it was found that the biosynthetic machineries of lichenicidin and haloduracin are highly specific to their dedicated peptide precursors. Likewise, the substitution of lichenicidin structural genes by chimeras of lichenicidin leader sequences and haloduracin core peptides did not yield mature haloduracin peptides. Despite these restrictions, it was found that the bifunctional enzyme HalT was able to process and export lichenicidin peptides. These findings corroborate the promiscuity of LanT enzymes reported for other lantibiotics, such as nukacin ISK-1 and lacticin 481.